Pseudorandom hypergraph matchings - Ehard, Stefan; Glock, Stefan; Joos, Felix (Combinatorics, probability & computing, 2020)
A celebrated theorem of Pippenger states that any almost regular hypergraph with small codegrees has an almost perfect matching. We show that one can find such an almost perfect matching which is ‘pseudorandom’, meaning that, for instance, the matching contains as many edges from a given set of edges as predicted by a heuristic argument.
Gesehen am 01.06.2022